Filosofia no ensino médio: a questão do conteúdo - Silva, Sérgio Pereira da (1994)
This dissertation is the result of work with the discipline Philosophy in High School, in public schools in the state network, in Uberlândia. In the daily life of this work, difficulties and obstacles of a political-pedagogical, administrative and theoretical nature were being made explicit, characterizing the existence of an impasse in the definition of content. It would, therefore, be necessary to identify this impasse and present a proposal to overcome it. In this sense, a historical description of the exclusion and return of Philosophy to High School in Minas Gerais was decided, believing that such contextualization is of fundamental importance. Then, the process of implementing Philosophy in the aforementioned section is analyzed, through the process of preparing a curricular proposal coordinated by the Secretary of State for Education. Despite this analysis, a detailed description of the current practice of this discipline was understood as timely. The experience that evidenced the content impasse was described. In order to present a proposal of alternative content, which could not only guide the teaching profession in an immediate manner, but also refer to possible discussions about the future of Philosophy as a school subject, fundamental concepts such as: man and his forms of knowledge; the concept of education; from school; High School; of Philosophy and its contents. Concluding this discussion, a content proposal for this discipline is presented. Therefore, the aim is not only to identify a pedagogical problem in a particular discipline, or to correct any philosophical mistakes, but to contribute to overcoming them in view of the permanence and credibility of this disciplinary content, by rescuing its identity and its competence.